Ethical Evaluation and Ethical Analysis – An Aspect of the Right Decisions in Business (UNWE Yearbook, 2014)
The study presents ethical evaluation and ethical analysis as a prerequisite for making the right decision in any business which makes this issue highly relevant. Targeted efforts to master them and implement in practice are seen in the context of the rational choice theory and the need to rationalize human relations in general, and in the economic sphere and business in particular.First the place of morality in the economy is justified, emphasizing the common signs and the interaction between them, and the causes of rising expectations towards moral regulator in the economic environment are analyzed then.Right decisions in business are presented as necessary and determined as a difficult balance of technological, economic, legal, and ethical correctness.Special attention is paid to ethical evaluation and to its role for the functioning of morals, for every human choice, and for decision making, while revealing its controversial character and the difficulties that accompany it.Ethical analysis is described as a means of reaching an objective ethical evaluation, and its "technology" is presented. Six important prerequisites that must be available for fruitful ethical analysis are considered and it is focused on three main approaches of the analysis – motivational, consequential and virtual-integrative; and the most used principles, as well - deontological and utilitarian.Ethical casuistry is viewed as an important aspect of business ethics and its characteristics are revealed, as well as the role of ethical analysis for the correct case solving. A model for ethical analysis of business cases is given, including eight important steps to follow. The acquisition of certain ethical skills and competence are presented as necessary for ethical analysis, for making the right decisions, and for good business practice. Teaching business ethics in economy oriented majors at the university has been cited as a reliable means to acquire ethical skills and ethical competence and to absorb some subtleties in the analysis of business cases and right decisions taking at all levels of business.The conclusion argues discussed efforts to ethical analysis and ethical evaluation as counteract to the general crisis of rationality and stimulus to promote socially responsible